Covid-19: The impact on the economy and policy responses: A review - Hanming Fang (Asian Development Bank Institute (ADBI), 2021)
The impact of the COVID-19 pandemic is far-reaching. In this paper, we selectively review the rapidly growing literature with a focus on (1) the impact of COVID-19 on the labor market, both in terms of overall employment and in terms of work-from-home arrangements; (2) how COVID-19 may impact the re-organization of the global supply chain; (3) how COVID-19 accelerated the digitization of the economy, and how this impacts the small and medium-sized businesses; and (4) government policy responses.
Keywords: I0; J0; H3; F6; 330; work from home; digitization; global supply chain; inequality; small and medium-sized businesses